Village Government Efforts in Realizing the Highest National Building Village Index (IDM) in Ngroto Village - Nefa Wahyuning Anggraini; Dhanny Septimawan Sutopo (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
Every government program certainly has the support of the local government to the bottom, such as the village government. Likewise, with the Village Building Index (IDM) program, of course, every local government is racing to succeed even, by all means, will try to get achievements from the program. But in the Ngroto Village Government, by carrying out village government functions as usual, by existing rules get achievements as a village with the highest IDM score at the National level in 2018. This research uses qualitative methods with the approach of intrinsic case study Robert K. Yin. Indeed, this approach received a lot of criticism since its emergence because it was considered weak analysis, not objective, and full of bias, but in research not only â€œwhy,â€ but also â€œhowâ€ Ngroto Village Government with its habit got maximum results. With this approach, researchers can explore and elaborate in-depth and comprehensively. The case study wants to know more deeply when the village government is not oriented towards achievement or achievement can become the village government with the highest national score. The village government applies legal regulations such as the implementation of musdes and musdus to filter aspirations and involve the community in planning development programs (participatory). Such efforts continue to be carried out by the village government to achieve achievements and are now a pilot center for other village governments.